2012
DOI: 10.1007/s11060-012-0943-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective phase II single-institution trial of sunitinib for recurrent malignant glioma

Abstract: Single-agent sunitinib, an oral small molecule inhibitor of multiple tyrosine kinase receptors, was evaluated for treatment of patients with recurrent glioblastoma (GB) and anaplastic astrocytoma (AA). Fourteen AA and 16 GB patients, all previously treated with surgery, radiotherapy, and temozolomide, were enrolled in a prospective phase II study at either first or second relapse. Patients were treated with daily sunitinib for 4 consecutive weeks, followed by a 2-week break. For AA patients, the most common si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…As a pan-inhibitor of VEGFR, particularly VEGFR2, sunitinib represents an attractive treatment option as an antiangiogenic drug in the therapy of glioma. However, clinical trials using sunitinib (Neyns et al, 2011;Pan et al, 2012) and several molecularly targeted agents (e.g., cediranib, pazopanib, vandetanib) have been unsuccessful in GBM therapy (Batchelor et al, 2010;Iwamoto et al, 2010;Kreisl et al, 2012). This may be due in part to the limited delivery of these agents across the BBB (Minocha et al, 2012a,b;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a pan-inhibitor of VEGFR, particularly VEGFR2, sunitinib represents an attractive treatment option as an antiangiogenic drug in the therapy of glioma. However, clinical trials using sunitinib (Neyns et al, 2011;Pan et al, 2012) and several molecularly targeted agents (e.g., cediranib, pazopanib, vandetanib) have been unsuccessful in GBM therapy (Batchelor et al, 2010;Iwamoto et al, 2010;Kreisl et al, 2012). This may be due in part to the limited delivery of these agents across the BBB (Minocha et al, 2012a,b;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown significant antitumor and antiangiogenic activity of sunitinib (Zhou et al, 2008;Zhou and Gallo, 2009). However, recent clinical trials have been disappointing (Neyns et al, 2011;Pan et al, 2012). One possibility for these conflicting results could be attributed to the lack of adequate drug delivery, mediated by the efflux transporters at the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…Small‐molecule tyrosine kinase inhibitors such as imatinib mesylate (which targets PDGFR‐α, PDGFR‐β, c‐kit, and c‐abl), sunitinib (which targets VEGFR1‐3, PDGFR‐α, PDGFR‐β, Kit, Fms‐like tyrosine kinase 3 [Flt‐3], and colony stimulating factor 1 receptor [CSF‐1R]), and bevacizumab (which targets VEGF‐A) have been proven successful in treating various other cancers . Most of these agents, however, have been tested with only limited success in GBM therapy . Other VEGFR/PDGFR inhibitors such as sorafenib, pazopanib, and vatalanib have shown no significant clinical benefit .…”
Section: Therapeutic Approaches and Outcomes To Datementioning
confidence: 99%
“…In 88% of all glioma genetic alterations affecting the receptor‐tyrosine kinases (RTKs)/RAS/phosphatidylinositide 3'‐OH kinase (PI3K) networks have been found . While sunitinib, a potent inhibitor of multiple RTKs, showed potent anti‐angiogenic and anti‐invasive effects in GBM cell lines, the results of these preclinical studies could not be translated into clinical success, suggesting, that targeting only one single aberrantly activated pathway is inefficient to overcome the dysregulated oncogenic signaling network. Likewise the mTOR inhibitor rapamycin, a downstream target of PI3K signaling, showed in several models growth inhibiting activity .…”
mentioning
confidence: 99%